The Influence of Brand Ambassadors and Brand Image on Purchase Intention Which Impacts Purchase Decisions on the Shopee Application - Muhammad Fahrel Novelyan; Febrianus David D Kerans; Dr. Osly Usman, M.Bus Syst (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study attempts to investigate the impact of brand ambassadors and brand image on purchase intention that greatly affect purchase decisions. With the aid of SmartPLS 3.0 software, the study takes a quantitative approach and applies the Structural Equation Modeling (SEM) method. In order to examine the connections between the variables, the research formulates and evaluates seven hypotheses. With a focus on the impact of brand ambassadors and brand image on purchase intention, this study attempts to investigate the elements and variables that greatly affect purchase decisions. The study's findings indicate important findings. First, Brand Ambassadors are found to have a positive and significant influence on Purchase Intention (original sample value of 0.511, P-Value = 0.000). Secondly, it is found that Brand Image has a significant impact on Purchase Intention (original sample value of 0.334, P-Value of 0.003). Additionally, it is shown that Purchase Decision is positively and significantly influenced by Brand Ambassador (P-Value of 0.010, original sample value of 0.276). In the context of digital marketing, this research advances our understanding of the relationships among brand ambassador, brand image, purchase intention, and purchase decision. For businesses using the Shopee app as a sales platform, the results offer insightful information that helps them maximize marketing tactics and brand ambassador use to improve sales results in the ever-changing market.